Peste des Petits Ruminants Viruses Re‐emerging in China, 2013–2014. Issue 5 (24th January 2015) - Wu, X.; Li, L.; Li, J.; Liu, C.; Wang, Q.; Bao, J. Y.; Zou, Y.; Ren, W.; Wang, H.; Zhang, Y.; Lv, Y.; Liu, F.; et al.
Summary: Re‐emergence of peste des petits ruminants (PPR) was officially reported in Xinjiang Uygur Autonomous Region in north‐western China in November 2013, and then along with the movements of goats and sheep, this disease rapidly spread to other provinces, autonomous regions and municipalities (P/A/M) of China. A total of 256 PPR‐affected counties in 22 P/A/M were identified up to September 2014. Phylogenetic analysis revealed that the current circulating strains and Tibet strains isolated previously in 2007, both belonged to lineage IV but in different sub‐branches. Nevertheless, compared with the Tibet strains, the current circulating strains shared high degree of genetic homology with those from Pakistan and Tajikistan.